Microstructural Formation and Creep Resistance of Sintered Titanium Aluminides with Co and Ni Addition - Warlen Alves Monfardini; Juliano Soyama (Materials Research)
One of the most effective approaches for the densification of titanium aluminides processed by powder metallurgy involves the addition of elements that induce the formation of a liquid phase during sintering. This work investigated the sintering behavior and creep resistance of Ti-45Al (in at.%) with ternary Co or Ni additions. Conventional sintering under a high vacuum atmosphere led to densifications of approximately 90% of the theoretical density in the Ti-45Al-2Co and Ti-45Al-2Ni alloys, while binary Ti-45Al was limited to a maximum of 57%. Microstructural analysis revealed the formation of equilibrium intermetallics γ-TiAl and α2-Ti3Al, along with Ni- and Co-rich regions concentrated at the boundaries of primary particles. Compression creep tests at 800°C under a 120 MPa load demonstrated a significant increase in mechanical strength, especially with the addition of Co, which showed 1% of plastic deformation in approximately 18 hours.